A girl walks home alone at night [videorecording (DVD)] - Amirpour, Ana Lily; Vand, Sheila; Marnò, Mozhan 1980-; Manesh, Marshall, 1950- (Kino Lorber, 2015)
The first Iranian Vampire Western ever made. A joyful mash up of genre, archetype, and iconography, its prolific influences span spaghetti westerns, graphic novels, horror films and the Iranian New Wave.